How Do Senators Vote? Disentangling the Role of Voter Preferences, Party Affiliation, and Senate Ideology - Levitt, Steven D. (American Economic Review, 1996)
This paper develops a methodology for consistently estimating the relative weights in senator utility functions, despite the fact that senator ideologies are unobserved. The empirical results suggest that voter preferences are assigned only one quarter of the weight in senator utility functions. The national 'party line' also has some influence but the senator's own ideology is the primary determinant of roll-call voting patterns. These results cast doubt on the empirical relevance of the median voter theorem. Estimation of the model requires only roll-call voting data, making it widely applicable. Copyright 1996 by American Economic Association.